Associations between early-life growth pattern and body size and follicular lymphoma risk and survival: a family-based case-control study. (October 2022) - Odutola, Michael K.; van Leeuwen, Marina T.; Turner, Jennifer; Bruinsma, Fiona; Seymour, John F.; Prince, H. Miles; Milliken, Samuel T.; Hertzberg, Mark; Trotman, Judith; Opat, Stephen S.; Lindeman, Robert; Roncolato, Fernando; et al.
Abstract: Background: The influence of early-life growth pattern and body size on follicular lymphoma (FL) risk and survival is unclear. In this study, we aimed to investigate the association between gestational age, growth during childhood, body size, changes in body shape over time, and FL risk and survival. Methods: We conducted a population-based family case-control study and included 706 cases and 490 controls. We ascertained gestational age, growth during childhood, body size and body shape using questionnaires and followed-up cases (median=83 months) using record linkage with national death records. We used a group-based trajectory modeling approach to identify body shape trajectories from ages 5–70. We examined associations with FL risk using unconditional logistic regression and used Cox regression to assess the association between body mass index (BMI) and all-cause and FL-specific mortality among cases. Results: We found no association between gestational age, childhood height and FL risk. We observed a modest increase in FL risk with being obese 5 years prior to enrolment (OR=1.43, 95 %CI=0.99–2.06; BMI ≥30 kg/m 2 ) and per 5-kg/m 2 increase in BMI 5 years prior to enrolment (OR=1.14, 95 %CI=0.99–1.31). The excess risk for obesity 5 years prior to enrolment was higher for ever-smokers (OR=2.00, 95 %CI=1.08–3.69) than never-smokers (OR=1.14, 95 %CI=0.71–1.84). We found no association between FL risk and BMI at enrolment, BMI for heaviest lifetime weight, the highest categories of adult weight or height, trouser size, body shape at different ages or body shape trajectory. We also observed no association between all-cause or FL-specific mortality and excess adiposity at or prior to enrolment. Conclusion: We observed a weak association between elevated BMI and FL risk, and no association with all-cause or FL-specific mortality, consistent with previous studies. Future studies incorporating biomarkers are needed to elucidate possible mechanisms underlying the role of body composition in FL etiology. Highlights: Obesity 5 years prior to enrolment and per 5-kg/m 2 increase in BMI 5 years prior to enrolment modestly increases follicular lymphoma (FL) risk. There is no association between gestational age, growth during childhood, adult height or weight, trouser size, body shape at different ages or body shape trajectories and FL risk. There is no evidence of an association between body mass index and all-cause or FL-specific mortality. Future studies should examine adiposity using objective, longitudinal measures of body composition and biomarkers.